2015
DOI: 10.1038/jp.2015.194
|View full text |Cite
|
Sign up to set email alerts
|

Maturational, comorbid, maternal and discharge domain impact on preterm rehospitalizations: a comparison of planned and unplanned rehospitalizations

Abstract: These four-domain models were more predictive than single domains. Many total readmission events were planned, suggesting parsing planned and unplanned rehospitalizations may benefit quality-improvement efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Although others have examined hospital readmission in preterm infants born in the past decade, our study is unique in that we have evaluated outpatient medical care, including ER and pediatric SS visits, in addition to inpatient readmission in a cohort of preterm infants born since 2005. 1,2,5,6,9,19 We have found that recurrent hosp and ER visits through the age of 2 years are primarily associated with extreme prematurity and PHI rather than specific neonatal morbidities, including BPD. Conversely, high SS use through the age of 2 years was associated with morbidities including ROP, NEC, and IVH and was associated with overall worse neurodevelopmental outcome.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although others have examined hospital readmission in preterm infants born in the past decade, our study is unique in that we have evaluated outpatient medical care, including ER and pediatric SS visits, in addition to inpatient readmission in a cohort of preterm infants born since 2005. 1,2,5,6,9,19 We have found that recurrent hosp and ER visits through the age of 2 years are primarily associated with extreme prematurity and PHI rather than specific neonatal morbidities, including BPD. Conversely, high SS use through the age of 2 years was associated with morbidities including ROP, NEC, and IVH and was associated with overall worse neurodevelopmental outcome.…”
Section: Discussionmentioning
confidence: 96%
“…[16][17][18] Despite these improvements, however, few studies have examined health care utilization in very preterm infants born in the past 10 years and these studies have examined only hospital readmission. 1,9,19 To our knowledge, no study has examined the relationship between health care utilization and neurodevelopmental outcome in a cohort of preterm infants since 2005. We, therefore, sought to describe the incidence and predictors of hosp, ER visits, and pediatric SS care, as well as their relationship to neurodevelopmental outcome in the first 2 years of life in a contemporary cohort of preterm infants.…”
mentioning
confidence: 99%
“…(13)(14)(15) Rehospitalisation rates amongst preterms have been found to be significantly higher than those of full-term infants. (16)(17)(18)Factors previously found to be associated with rehospitalisation are male sex (19)(20)(21)(22), lower gestational age (23)(24)(25), low birth weightor being small for gestational age (SGA) (26), feeding problems (27)(28)(29)(30), bronchopulmonary dysplasia (BPD) (31,32)and lower socioeconomic status (21,27,33,34). To the best of our knowledge, the literature on the early rehospitalisation of preterms discussed explanatory models only and not validated predictive models.…”
Section: Introductionmentioning
confidence: 99%
“…(13)(14)(15) Rehospitalisation rates amongst preterms have been found to be significantly higher than those of full-term infants. (16)(17)(18) Factors previously found to be associated with rehospitalisation are male sex (19)(20)(21)(22), lower gestational age (23)(24)(25), low birth weight or being small for gestational age (SGA) (26), feeding problems (27)(28)(29)(30), bronchopulmonary dysplasia (BPD) (31,32) and lower socioeconomic status (21,27,33,34). To the best of our knowledge, the literature on the early rehospitalisation of preterms discussed explanatory models only and not validated predictive models.…”
Section: Introductionmentioning
confidence: 99%